Aceh Islamic Society And Communication: Beliefs In Animism And Dynamism - Ridwan Muhammad Hasan Ridwan Muhammad Hasan (Jurnal Komunikasi dan Media, 2024)
The Aceh community was the community that like that fanatical with the current and the traditional belief, the tradition and the Hindu teaching culture, They were also still gripping tight to the religious teaching that was left by the previous person, although that carried this teaching not came from the Islam religion, for this reason in a manner indirectly this belief, could form private in life every day that very much did not make an impression. In a community's Aceh part that lives in the countryside territory up to now, was still carrying out the tradition and the culture that were confused than the legacy of the Hindu teaching like, the good deeds heresy, superstition and superstition and has become a good deed in his days that were difficult to left. In a community's Aceh part that lives in the countryside territory up to now, was still carrying out the tradition and the culture that were confused than the legacy of the Hindu teaching like, the good deeds heresy, superstition and superstition and has become a good deed in his days that were difficult to left. In general, he, the Aceh traditional community still belief and trusted that the genie's kind in various forms like jen apui, the burong, geunteut, beunot and burong tujoh. They also still trusted that the person's soul who died in the situation was very frightening as being killed, died was bloody, died sank, died fell from the tree trunk etcetera, will change, into the ghost.